2021
DOI: 10.3390/en14248206
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Realistic Boundary Conditions at the Combustion Chamber/Turbine Interface Using Large-Eddy Simulation

Abstract: Numerical simulation of multiple components in turbomachinery applications is very CPU-demanding but remains necessary in the majority of cases to capture the proper coupling and a reliable flow prediction. During a design phase, the cost of simulation is, however, an important criterion which often defines the numerical methods to be used. In this context, the use of realistic boundary conditions capable of accurately reproducing the coupling between components is of great interest. With this in mind, this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The LES result of combustor is sensitive to the inlet/outlet condition and the wall boundary condition, and the requirements for the accuracy of the boundary condition are very high in the simulation prediction of the advanced combustors. Various methods have been proposed to improve inlet/outlet conditions while implementing coupling approaches with other components including compressors and turbines (Boudier et al , 2008; Martin et al , 2021; McGuirk, 2014). Today, 3D performance evaluation based on CFD occupies an important place in combustor design due to its comprehensiveness and reliability, and is applied to the design and development of most combustors.…”
Section: Combustor Design Methodsmentioning
confidence: 99%
“…The LES result of combustor is sensitive to the inlet/outlet condition and the wall boundary condition, and the requirements for the accuracy of the boundary condition are very high in the simulation prediction of the advanced combustors. Various methods have been proposed to improve inlet/outlet conditions while implementing coupling approaches with other components including compressors and turbines (Boudier et al , 2008; Martin et al , 2021; McGuirk, 2014). Today, 3D performance evaluation based on CFD occupies an important place in combustor design due to its comprehensiveness and reliability, and is applied to the design and development of most combustors.…”
Section: Combustor Design Methodsmentioning
confidence: 99%
“…The authors demonstrated that, even if the results seemed to be quite insensitive to the different turbulent injections, the CFD predictions obtained by simulating the stand-alone first stage were highly impacted by the imposed mean boundary conditions, confirming the importance of employing a coupled approach or imposing boundary conditions that are as realistic as possible. As a matter of fact, in the context of the project FACTOR, Martin et al [41,42] generated a database of unsteady inlet boundary conditions under laboratory non-reactive conditions for the isolated NGV. To achieve this, the data were recorded at the interface plane between the combustor and nozzle from a fully coupled LES simulation including both components.…”
Section: Introductionmentioning
confidence: 99%